Adapting the Army's Training and Leader Development Programs for Future Challenges - Crowley, James C. (RAND Corporation, 2013)
In addition to the defeat of conventional enemy forces, Army units and leaders must be able to defeat unconventional forces, develop partner forces, protect local populations, and support civil functions. This report examines the adequacy of the Army Training and Leader Development (ATLD) system management processes, identifies areas for improvement, and develops directions that the Army could take to improve its ATLD management processes.